Percepção de estresse, Síndrome de Burnout e estratégias de enfrentamento em cuidadores de pessoas idosas institucionalizadas - Silva, Adrielli Fernanda de Oliveira e (2023)
Introduction: Despite their technical skills and knowledge in the field, healthcare professionals working in direct care for institutionalized elderly individuals are more prone to stress and burnout syndrome. These conditions can be modulated through various coping strategies. Objective: To analyze the perception of personal stress and burnout syndrome among formal caregivers of institutionalized elderly individuals and their relationship with coping strategies. Method: This is a quantitative cross-sectional study. The research was conducted in three philanthropic long-term care facilities in the city of Ribeirão Preto, located in the state of São Paulo, with 54 professionals involved in the direct care of institutionalized elderly individuals (caregivers, aides, and nursing technicians). Data collection was carried out online from September to October 2022. After agreeing to participate in the research by digitally signing the Informed Consent Form, participants received a link to complete questionnaires regarding sociodemographic, economic, clinical, and professional characteristics. Additionally, they were assessed for perceived stress (Perceived Stress Scale - PSS-14), burnout syndrome (Maslach Burnout Inventory: Human Services Survey - MBI-HSS), and coping strategies (Occupational Coping Scale - OCS). Data were analyzed using descriptive and correlational statistics. Ethical considerations were observed throughout the data collection and analysis process. Results: The majority of formal caregivers were female (85.2%), with a median age of 43 [36.25, 51.75] years, working as nursing assistants (74.1%), married (46.3%), having completed high school (50%), working 40 hours per week (64.8%), earning 1 to 3 minimum wages per month (61.1%), and having worked as caregivers in the institution for more than 10 years (29.6%). Regarding health data and the applied scales, the majority reported engaging in physical activity (59.35), having low back pain (25.9%), and experiencing insomnia (18.5%). The median score on the EEP-14 scale was 22 [17, 27], with an absence of perceived stress. The total MBI score was 60 [54, 64], with a moderate level of emotional exhaustion (median of 24), a depersonalization score of 11 points (moderate), and a personal accomplishment score of 23.5 (high level). As for the assessment of coping strategies (ECO), a total score of 91.8 [70.25, 114.75] was obtained, with the control strategy being the most frequently used, at 43 [38.25, 48]. When associating the scores of the three scales, a trend was found in which higher ECO scores were associated with lower EEP, independently of MBI. Conclusions: The data reveal that the group assessed in this study demonstrates a low perception of stress and a moderate to high level of burnout, highlighting the need for actions that promote awareness and sensitivity regarding stress and burnout, as well as their symptoms and impacts on both personal and professional life. Thus, fostering the development of effective coping mechanisms and problem-solving skills to manage stressful events, reduce negative emotions, and mitigate psychosocial work-related demands.